Analisa Pengaruh Beban Kendaraan Terhadap Kerusakan dan Umur Rencana Jalan - Ahmad refi; Angelalia Roza; Anggun Pratiwi JF; Katrun Nada Salsabila; Andi Mulya Rusli (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
The Km-18 of Padang Bypass Road is an Arterial road class III-A. This road is burdened by heavy vehicles which carrying loads that exceed the permitted capacity. This activity can lead to road damage and a reduction in road life. This study aims to analyze the effect of traffic loads that exceed permitted capacity on road conditions, including the remaining life of the pavement and the degree of road damage. The primary data used is data on road damage conditions such as the discharge of road surface grains, potholes, and grooves. Secondary data used is in the form of LHR data for 2017 and 2018, also, the vehicle weight data obtained from P2JN West Sumatra Province. The analytical approach uses the 1993 AASHTO method in the form of a cumulative analysis of the 10-year ESAL plan, by the traffic design for flexible pavement. The result of this study indicates that the Km-18 of Padang Bypass Road has decreased 7.58% of its design life in 2020. The cumulative plan ESAL value is 70,792,016.05 and the cumulative ESAL overloading value is 192,394,000.9. The Truck factor (TF) in normal condition is 0.8176692, but in overloading condition, it is 6.1375255. The road life predicted to be ended in year 4 (in 2024), although it planned to end in 2027.